Integrating Science and Islam: Development of Teaching Materials for Environmental Chemistry Courses - Muslim, Buchori; Nahadi, Nahadi; Anwar, Sjaeful; Munawaroh, Heli Siti Halimatul; Nuraeni, Neng Sri (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2023)
AbstractThe teaching materials on chemistry integrated into Islam are not yet available at the university level. Teaching materials can be used in learning activities. This study aims to develop integrated Islamic chemistry teaching materials for environmental chemistry courses. This research uses the Four Steps Material Teaching Development method (4STMD). 4STMD consists of four stages, namely the selection stage, structuring stage, characterisation stage, and reduction stage. At the stage of selection and structuring, the results of integration between environmental chemistry subjects and the Qur’an, Hadith, Fiqih, and Aqeedah Morals are obtained. At the characterisation stage, the concepts tested have easy characteristics, with an overall score of 86.9%. Based on the characterisation test results, the reduction phase in this research was not carried out because all concepts have easy characteristics. The completed teaching materials are then tested for feasibility by experts based on material aspects, presentation, language, and graphics. Based on the results of the feasibility test of the teaching materials, the average score is 95%. This shows that the teaching materials are considered worthy with a ‘very good’ predicate.AbstrakBahan ajar kimia terintegrasi keislaman belum tersedia di tingkat Universitas. Bahan ajar dapat digunakan dalam kegiatan pembelajaran. Penelitian ini bertujuan untuk mengembangkan bahan ajar kimia terintegrasi keislaman pada Mata Kuliah Kimia Lingkungan. Penelitian ini menggunakan metode Four Steps Teaching Material Development (4STMD). 4STMD terdiri dari empat tahapan, yaitu tahap seleksi, tahap strukturisasi, tahap karakterisasi, dan tahap reduksi. Pada tahap seleksi dan strukturisasi, didapatkan hasil integrasi antara mata kuliah kimia lingkungan dengan Al Qur’an, Hadits, Fikih, dan Akidah Akhlak. Pada tahap karakterisasi, keseluruhan konsep yang diujikan memiliki karakteristik mudah, dengan nilai keseluruhan rata-rata sebesar 86,9%. Berdasarkan hasil uji karakterisasi, tahap reduksi pada penelitian ini tidak dilakukan karena seluruh konsep memiliki karakteristik mudah. Bahan ajar yang telah selesai disusun selanjutnya di uji kelayakannya oleh ahli berdasarkan aspek materi, penyajian, bahasa, dan grafika. Berdasarkan hasil uji kelayakan bahan ajar, didapatkan nilai rata-rata sebesar 95%. Hal ini menunjukkan bahwa bahan ajar dinyatakan layak dengan predikat sangat baik.How to Cite: Muslim, B., Nahadi, Anwar, S., Munawaroh, H.S.H., & Nuraeni, N.S (2023). Integrating Science and Islam : Development of Teaching Materials for Environmental Chemistry Courses. TARBIYA: Journal of Education in Muslim Society, 10(2), 207-218. doi:10.15408/tjems.v10i2.32210.